A refined paleotemperature calibration for New Zealand limnic environments using differentiation of branched glycerol dialkyl glycerol tetraether (brGDGT) sources - Zink, K.; Vandergoes, M.; Bauersachs, T.; Newnham, R.; Rees, A.; Schwark, Lorenz (John Wiley & Sons, 2016)
Copyright © 2016 John Wiley & Sons, Ltd.Branched glycerol dialkyl glycerol tetraethers (brGDGTs) were abundant in surface sediments of freshwater lakes and in catchment soils at altitudes from 10 to 2020 m in New Zealand. Significant differences in brGDGT compositions between lake sediments and soils indicate sources from separate microbial habitats. An expanded modern calibration dataset comprising 33 lakes has enabled a revised calibration function for determining past mean annual air temperature (MAT) from brGDGTs in New Zealand lake sediments: MAT (°C) = -31.664 × MBTm + 16.252 (n = 30). The function uses a modified methylation index of branched tetraethers (MBTm) that incorporates brGDGT III in the numerator to overcome the lower correlation found between our larger dataset and the unmodified MBT which had been used for previous calibrations. Calibrations combining the cyclization index of branched tetraethers (CBT) and the MBTm or using only certain brGDGTs are possible but have limitations. The revised function shows slightly higher correlation with MAT (R2 = 0.75) than previous calibrations, which were based on nine sites. The refined calibration function is applied to a ~16 000-year lake sediment sequence from northern South Island, New Zealand, and yields temperature reconstructions that are consistent with independently derived climate trends from the same sequence.